On dating rock paintings in the uKhahlamba-Drakensberg and the Biggarsberg - Jolly, P. (Southern African Humanities, 2021)
To cite this comment: Jolly, P. 2004. On dating rock paintings in the uKhahlamba-Drakensberg and the Biggarsberg. Southern African Humanities 16: 37-8.